Open Source Software (OSS) for Creation of Digital Library Repositories - K N, Madhu; Kumar B M, Lakshana; -, Senthilnayagam (International Journal of Information Studies, 2025)
Now days organizations cannot think of doing their tasks effectively and efficiently without software. The extremely competitive environment, zero deficiency and enhanced productivity has made it mandatory for the organizations to carefully choose the appropriate software after comprehensive needs assessment. Software simply their tasks and saves a lot of precious time which can be utilized in managing other important issues. Libraries also need softwares if they want to create a parallel digital library with features which we may not find in a traditional library. There are several open source softwares available to create a digital library repository. For this, firstly the library professionals should be aware of the advantages of open source software and should involve in their development. They should have basic knowledge about the selection, installation and maintenance. Open source software requires a greater degree of computing responsibility than commercial software. Digitization involves huge money to create and maintain and the OSS appears to be a means to reduce it. Among these, DSpace and Greenstone are becoming more popular in India and abroad. This paper deals with the open source softwares, Advantages of Open Source Software, Desirable features of DL Software and Digital repository created by OSS in India.